Pemberian Kulit Biji Kopi dalam Ransum Sapi Aceh Terhadap Kecernaan secara In Vitro - Yunasri Usman; M. Nur Husin; Riantia Ratni (Jurnal Agripet, 2013)
The supplementation peel coffee beans in the ration Aceh cattle on in vitro digestibilityABSTRACT. This research was carried out at the Laboratory of Feed and Animal Nutrition, Department of Animal Husbandry Faculty of Agriculture Syiah Kuala University for 73 days from December 26, 2011 to March 7, 2012. The purpose of this experiment was to find out the effects of the coffee peeling on in vitro digestibility of Aceh beef cattle. Completely Randomized Design (CRD) was applied in this experiment consisting of 4 treatments namely levels of coffee peeling on basal diet (R0=0%, R1=10%, R2=20%, R3=30%). Each treatment consists of 5 replications. Parameters observed in this research were dry and organic matter digestibility. The results showed that dry matter digestibility was not significantly different (P0,05)amongst treatments 54,42%, 49,32%, 45,97%, 42,08%) for R0, R1, R2 and R3 respectively. On the other hand, organic metter digestibility was significantly different (P0,05) in which R2 treatment was the highest and R0 treatment was the lowest (54,59%).